2002
DOI: 10.1038/sj.bjc.6600541
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic mechanisms in T47D and MCF-7 human breast cancer cells

Abstract: To investigate the mechanisms underlying apoptosis in breast cancer cells, staurosporine was used as an apoptotic stimulus in the human breast cancer cell lines MCF-7 and T47D. Staurosporine induced dose and time dependent increases in DNA fragmentation which was abrogated by z-VAD-fmk. MCF-7 cells did not express caspase-3, suggesting that DNA fragmentation occurred in the absence of caspase-3 and that other caspases may be involved. Staurosporine induced DEVDase activity in T47D cells suggesting the involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(126 citation statements)
references
References 45 publications
8
116
1
1
Order By: Relevance
“…These results contrast with some previous reports of NSAID-induced growth inhibition and apoptosis in breast and endometrial cancer cells (Noguchi et al, 1995;Planchon et al, 1995;Han et al, 1998;Arango et al, 2001), but these differences are reconciled by considering that these studies used NSAIDs other than aspirin (Noguchi et al, 1995;Planchon et al, 1995;Han et al, 1998), while others only observed apoptosis after long exposures (48 -96 h) to high concentrations of salicylate out with the therapeutic range (Sotiriou et al, 1999;Arango et al, 2001). The non-CRC cell lines are susceptible to other apoptosis-inducing agents and NFkB activators such as staurosporine and TNFa, respectively, indicating that these cell lines are not generally resistant to apoptosis or NFkB modulation (Mooney et al, 2002;Tang et al, 2002). The observation that aspirin decreased cell viability in one of the three breast cancer cell lines (T47D) is in keeping with epidemiological data that suggest a lesser protective effect of NSAIDs against breast cancer.…”
Section: Discussionsupporting
confidence: 77%
“…These results contrast with some previous reports of NSAID-induced growth inhibition and apoptosis in breast and endometrial cancer cells (Noguchi et al, 1995;Planchon et al, 1995;Han et al, 1998;Arango et al, 2001), but these differences are reconciled by considering that these studies used NSAIDs other than aspirin (Noguchi et al, 1995;Planchon et al, 1995;Han et al, 1998), while others only observed apoptosis after long exposures (48 -96 h) to high concentrations of salicylate out with the therapeutic range (Sotiriou et al, 1999;Arango et al, 2001). The non-CRC cell lines are susceptible to other apoptosis-inducing agents and NFkB activators such as staurosporine and TNFa, respectively, indicating that these cell lines are not generally resistant to apoptosis or NFkB modulation (Mooney et al, 2002;Tang et al, 2002). The observation that aspirin decreased cell viability in one of the three breast cancer cell lines (T47D) is in keeping with epidemiological data that suggest a lesser protective effect of NSAIDs against breast cancer.…”
Section: Discussionsupporting
confidence: 77%
“…The overt PCD II response in MCF-7 cells may be due to lack of caspase-3 activity and possible defects in apoptosome formation/ caspase-9 activation, although studies have shown that restoration of caspase-3 expression only partially restores apoptosis in these cells. 11 Furthermore, breast cancers expressing normal caspase-3, such as T47D, also mount an autophagic response to a variety of therapeutics, including DNA-damaging agents (Figure 8 and Mooney et al 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by an earlier report that STS induces the apoptosis of MCF-7, a caspase 3-deficient cell line, by the activation of caspase 6. 28 Moreover, Gal3 and Gal3(Y79FY118F) were expressed in c-Abl/Arg-depleted cells (Supplementary Figure 4a). In (Figure 6e).…”
Section: Resultsmentioning
confidence: 99%